Bacterioferritin: Structure, Dynamics, and Protein–Protein Interactions at Play in Iron Storage and Mobilization - Rivera, Mario (Accounts of chemical research, 2017)
Despite its essentiality to life, iron presents significant challenges to cells: the exceedingly low solubility of Fe3+ limits its bioavailability, and the reactivity of Fe2+ toward H2O2 is a source of the toxic hydroxyl radical (HO•). Consequently, cellular levels of free iron are highly regulated to ensure sufficiency while preventing iron-induced toxicity. Relatively little is known about the fate of iron in the bacterial cytosol or how cells balance the need for relatively high cytosolic iron concentrations with the potential toxicity of the nutrient. Iron storage proteins are integral to iron metabolism, and bacteria utilize two types of ferritin-like molecules to store iron, bacterial ferritin (Ftn) and bacterioferritin (Bfr). Ftn and Bfr compartmentalize iron at concentrations far above the solubility of Fe3+ and protect the reducing cell environment from unwanted Fe3+/Fe2+ redox cycling. This Account focuses on our laboratory’s efforts to study iron storage proteins in the model bacterium Pseudomonas aeruginosa, an opportunistic pathogen. Prior to our studies, it was thought that P. aeruginosa cells relied on a single Bfr assembled from two distinct subunits coded by the bfrA and bfrB genes. It is now known that, like in most bacteria, two iron storage proteins coexist in P. aeruginosa cells, a bacterial Ftn (FtnA), coded by the ftnA (formerly bfrA) gene and a bacterioferritin (BfrB), coded by the bfrB gene. Studies with BfrB showed that Fe2+ oxidation occurs at ferroxidase centers (FCs), followed by gated translocation of Fe3+ to the interior cavity, a process that is, surprisingly, distinct from that observed with the extensively studied Bfr from Escherichia coli, where the FCs are stable and function only as a catalytic site for O2 reduction. Investigations with BfrB showed that the oxidation of Fe2+ at FCs and the internalization of Fe3+ depend on long-range cooperative motions, extending from 4-fold pores, via B-pores, into FCs. It remains to be seen whether similar studies with E. coli Bfr will reveal distinct cooperative motions contributing to the stability of its FCs. Mobilization of Fe3+ stored in BfrB requires interaction with a ferredoxin (Bfd), which transfers electrons to reduce Fe3+ in the internal cavity of BfrB for subsequent release of Fe2+. The structure of the BfrB/Bfd complex furnished the only known structure of a ferritin molecule in complex with a physiological protein partner. The BfrB/Bfd complex is stabilized by hot-spot residues in both proteins, which interweave into a highly complementary hot region. The hot-spot residues are conserved in the sequences of Bfr and Bfd proteins from a number of bacteria, indicating that the BfrB/Bfd interaction is of widespread significance in bacterial iron metabolism. The BfrB/Bfd structure also furnished the only known structure of a Bfd, which revealed a novel helix-turn-helix fold different from the β-strand and α-helix fold of plant and vertebrate [2Fe–2S]-ferredoxins. Bfds seem to be unique to bacteria; consequently, although mobilization of iron from eukaryotic ferritins may also be facilitated by protein–protein interactions, the nature of the protein that delivers electrons to the ferric core of eukaryotic ferritins remains unknown.